The use of RNA‐based 5'‐aminolevulinate synthase 2 biomarkers in dried blood spots to detect recombinant human erythropoietin microdoses. Issue 5 (7th July 2021) - Loria, Francesco; Cox, Holly D.; Voss, Sven C.; Rocca, Angela; Miller, Geoffrey D.; Townsend, Nathan; Georgakopoulos, Costas; Eichner, Daniel; Kuuranne, Tiia; Leuenberger, Nicolas
Abstract: The hematological module of the Athlete Biological Passport (ABP) is used for indirect detection of blood manipulations; however, the use of this method to detect doping, such as with microdoses of recombinant human erythropoietin (rhEPO), is problematic. For this reason, the sensitivity of ABP must be enhanced by implementing novel biomarkers. Here, we show that 5'‐aminolevulinate synthase 2 ( ALAS2 ) mRNAs are useful transcriptomic biomarkers to improve the indirect detection of rhEPO microdosing. Moreover, the sensitivity was sufficient to distinguish rhEPO administration from exposure to hypoxic conditions. Levels of mRNAs encoding carbonate anhydrase 1 ( CA1 ) and solute carrier family 4 member 1 ( SLC4A1 ) RNA, as well as the linear (L) and linear + circular (LC) forms of ALAS2 mRNA, were monitored for 16 days after rhEPO microdosing and during exposure to hypoxic conditions. ALAS2 mRNAs increased by 300% compared with the baseline values after rhEPO microdosing. Moreover, ALAS2 mRNAs were not significantly increased under hypoxic conditions. By contrast, CA1 mRNA was increased after both rhEPO microdosing and hypoxia, whereas SLC4A1 mRNA did not significantly increase under either condition. Furthermore, the analyses described here were performed using dried blood spots (DBSs), which provide advantages in terms of the sample collection, transport, and storage logistics. This study demonstrates that ALAS2 mRNA levels are sensitive and specific transcriptomic biomarkers for the detection of rhEPO microdosing using the hematological module of the ABP, and this method is compatible with the use of DBSs for anti‐doping analyses.